Emerging Roles of microRNAs as Biomarkers and Therapeutic Targets for Diabetic Neuropathy - Fan, Baoyan; Chopp, Michael; Zhang, Zheng Gang; Liu, Xian Shuang (Frontiers in Neurology, 2020)
Diabetic neuropathy (DN) is the most prevalent chronic complication of diabetes mellitus. The exact pathophysiological mechanisms of DN are unclear; however, communication network dysfunction among axons, Schwann cells, and the microvascular endothelium likely play an important role in the development of DN. Mounting evidence suggests that microRNAs (miRNAs) act as messengers that facilitate intercellular communication and may contribute to the pathogenesis of DN. Deregulation of miRNAs is among the initial molecular alterations observed in diabetics. As such, miRNAs hold promise as biomarkers and therapeutic targets. In preclinical studies, miRNA-based treatment of DN has shown evidence of therapeutic potential. But this therapy has been hampered by miRNA instability, targeting specificity, and potential toxicities. Recent findings reveal that when packaged within extracellular vesicles, miRNAs are resistant to degradation, and their delivery efficiency and therapeutic potential is markedly enhanced. Here, we review the latest research progress on the roles of miRNAs as biomarkers and as potential clinical therapeutic targets in DN. We also discuss the promise of exosomal miRNAs as therapeutics and provide recommendations for future research on miRNA-based medicine.